SHARIA GOVERNANCE DAN KINERJA LEMBAGA KEUANGAN SYARIAH: FIRM SIZE SEBAGAI PEMODERASI - Febri Rahmi; Leny Nofianti; Andi Irfan; Desrir Miftah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Islamic Banking has astrategic rolein improving the welfare of the people, through theintermediation process of lending and funding distribution activities and the provision of other financial services, based on the principles of sharia. The study looked at the relationship between the application of the principles of Shari'ah governance and performance of Islamic financia linstitutions in Riau. In this study, the performance of Islamic banking financial institutions measuredusing the Balanced Scorecard. The research was conducted on Islamic banking institutions in Riau, both Islamic Banks (BUS) and Sharia (UUS) successfully collected the data by 35 respondents. This study shows that sharia governance is able to influence the performance of sharia financial institutions in Riau Province as evidenced by a coefficient of 5.008 with a significance level of 0.000 much smaller than the value of α (0.05). The results of this next study indicate that sharia governance is not able to influence the performance of Islamic financial institutions in Riau Province after being moderated by firm size as evidenced by a coefficient of -1.933 with a significance level of 0.071 greater than the value of α (0.05).